Efforts of Islamic Boarding Schools in Improving Inner Peace of The Elderly Through The Concept of Qolbu Management - Gheriyya Rahima; Wawan Hermawan; Risris Hari Nugraha (Fakultas Agama Islam Universitas Billfath, 2025)
This research aims to analyze the implementation of the concept of Manajemen Qolbu at Pondok Pesantren Daarut Tauhiid Bandung to enhance the inner peace of elderly students in the Golden Age Pesantren Program. This research employs a mixed method, involving 20 elderly students from PMK Batch 67, aged between 45 and 80 years. Data were collected through participatory observation, in-depth interviews, and open-ended questionnaires. Based on the analysis of the obtained data, it was found that the implementation of Manajemen Qolbu at PMK Daarut Tauhiid has a significant positive impact on the inner peace of elderly students. As many as 74% of the students reported improved emotional management, 85-90% experienced better inner peace, and 57.1% felt stronger in facing life's challenges. This program also contributed to the enhancement of the quality of worship and spiritual closeness to Allah, with 78% of participants feeling closer to God after participating in the program. This research concludes that Manajemen Qolbu not only helps the elderly overcome anxiety and fear but also empowers them to lead a more meaningful life. Recommendations from this study include the application of the concept of Manajemen Qolbu in Islamic educational institutions to expand its benefits, particularly for the elderly in society, as well as developing more systematic and sustainable programs to support the inner well-being of the elderly.